Satisfaction with life and psychological distress during the COVID-19 pandemic: An Egyptian online cross-sectional study - Ahmed H. El-Monshed; Ahmed Loutfy; Moustafa T. Saad; Ahmed S. Ali; Abdel-H; Ahmed Soliman Mohamed; Mahmoud Salah; Mohamed Zoromba (AOSIS, 2022)
Background: Coronavirus disease 2019 (COVID-19) is a novel sickness that emerged worldwide as an unprecedented crisis and led to major effects on the daily life of the general public as well as negative impacts on their mental well-being. Aim: This study aimed to assess satisfaction with life and psychological distress during the COVID-19 pandemic in Egypt. Setting: An online study was conducted in Egypt. Methods: A cross-sectional online survey was fulfilled by 1056 Egyptian adults from 06 to 13 June 2020. Psychological distress and satisfaction with life were measured by Arabic validated versions of the Kessler Psychological Distress Scale (K10) and the Satisfaction with Life Scale (SWLS). Results: About half of the surveyed respondents (51%) were satisfied with their life, whilst 57.4% experienced severe psychological distress. The independent predictors of satisfaction with life are being married, satisfactory income, low distress, moderate distress and high distress (adjusted odds ratio [AOR] = 1.2, 3.0, 2.5, 6.9, 5.2 and 2.1, respectively). Being a female, having secondary education, secondary education, unsatisfactory income and presence of mental illness are the independent predictors of mental distress (AOR = 2.3, 3.9, 1.9, 1.9, 1.6 and 4.0, respectively). Conclusion: The study provides evidence about the high prevalence of psychological distress during the peak period of Egypt's COVID-19 pandemic. The study results highlight the enhancement of development interventions to promote psychological well-being and feeling of satisfaction with life during the pandemic.